Carmen Blacker: Scholar of Japanese Religion, Myth and Folklore : Writings and Reflections - Blacker, Carmen (Book collections on Project MUSE., 2017)
Carmen Blacker was an outstanding scholar of Japanese culture, known internationally for her writings on religion, myth and folklore -- her most notable work being The Catalpa Bow: A Study of Shamanistic Practices in Japan. This volume contains a wide selection of writings in celebration of her work, including contributions from Donald Keene, Ben-Ami Shillony and Peter Kornicki, together with various essays and papers by Carmen Blacker herself that have hitherto not been widely available. Importantly, the volume contains significant extracts from the author's diaries over a period of more than forty years, together with a plate section drawn from the her extensive photographic archive. This volume offers a rare opportunity to gain such a close insight into an author's life and work.